2021
DOI: 10.1038/s42003-021-01943-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D upregulates the macrophage complement receptor immunoglobulin in innate immunity to microbial pathogens

Abstract: Vitamin D deficiency remains a global concern. This ‘sunshine’ vitamin is converted through a multistep process to active 1,25-dihydroxyvitamin D3 (1,25D), the final step of which can occur in macrophages. Here we demonstrate a role for vitamin D in innate immunity. The expression of the complement receptor immunoglobulin (CRIg), which plays an important role in innate immunity, is upregulated by 1,25D in human macrophages. Monocytes cultured in 1,25D differentiated into macrophages displaying increased CRIg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…More recent work has shown that vitamin D can activate antimicrobial activity in both human monocytes and macrophages through the induction of cathelicidin following TLR2/1 heterodimer activation ( Liu et al., 2006 ; Liu et al., 2007 ). Phagocytic capacity has also been shown to increase in macrophages treated with 1,25(OH) 2 D 3 , perhaps through upregulation of complement receptor immunoglobulin (CRIg) ( Small et al., 2021 ). This mechanism could support the finding in our study showing a significant increase in total MAP uptake for clinical animals, as other recent reports have described CRIg functioning as a pattern recognition receptor (PRR) for gram-negative bacteria and parasites ( Zeng et al., 2016 ; Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has shown that vitamin D can activate antimicrobial activity in both human monocytes and macrophages through the induction of cathelicidin following TLR2/1 heterodimer activation ( Liu et al., 2006 ; Liu et al., 2007 ). Phagocytic capacity has also been shown to increase in macrophages treated with 1,25(OH) 2 D 3 , perhaps through upregulation of complement receptor immunoglobulin (CRIg) ( Small et al., 2021 ). This mechanism could support the finding in our study showing a significant increase in total MAP uptake for clinical animals, as other recent reports have described CRIg functioning as a pattern recognition receptor (PRR) for gram-negative bacteria and parasites ( Zeng et al., 2016 ; Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D induces the expression of antimicrobial proteins such as cathelicidin and β-defensin-2 [46,47], playing an important role in the first response to microbial infections On the other hand, vitamin D skews the polarization of monocytes to a less pro-inflammatory phenotype, altering the cytokine secretion profile by changing the MAPK1 signaling [48,49]. Additionally, vitamin D impairs the maturation of monocytes to dendritic cells [50], while favoring the phagocytic capacity of macrophages though the induction of complement receptors [51].…”
Section: Effect On Innate Immune Cellsmentioning
confidence: 99%
“…Together, vitamin D promotes innate immunity through the expression of cathelicidin and β-defensin, improves autophagy, accelerates and cooperates with IFN, and affects complement activation [59].…”
Section: Antiviral Activity Of Vitamin D and The Innate Immune Responsementioning
confidence: 99%